Origin of multistate resistive switching in Ti/manganite/SiO x /Si heterostructures - Roman Acevedo, Wilson Stibens (2017)
We report on the growth and characterization of Ti/La1/3Ca3/2MnO3/SiO2/n-Si memristive devices.We demonstrate that using current as electrical stimulus unveils an intermediate resistance state, inaddition to the usual high and low resistance states that are observed in the standard voltagecontrolled experiments. Based on thorough electrical characterization (impedance spectroscopy,current-voltage curves analysis), we disclose the contribution of three different microscopic regionsof the device to the transport properties: an ohmic incomplete metallic filament, a thin manganitelayer below the filament tip exhibiting Poole-Frenkel like conduction, and the SiOx layer with anelectrical response well characterized by a Child-Langmuir law. Our results suggest that the existenceof the SiOx layer plays a key role in the stabilization of the intermediate resistance level, indicatingthat the combination of two or more active resistive switching oxides adds functionalities inrelation to the single-oxide devices. We understand that these multilevel devices are interesting andpromising, as their fabrication procedure is rather simple and they are fully compatible with thestandard Si-based electronics.